Mucus, commensals, and the immune system. (31st December 2022) - Zhao, Qing; Maynard, Craig L.
ABSTRACT: The immune system in the large intestine is separated from commensal microbes and comparatively rare enteric pathogens by a monolayer of diverse epithelial cells overlaid with a compact and adherent inner mucus layer and a looser outer mucus layer. Microorganisms, collectively referred to as the mucus-associated (MA) microbiota, physically inhabit this mucus barrier, resulting in a dynamic and incessant dialog to maintain both spatial segregation and immune tolerance. Recent major findings reveal novel features of the crosstalk between the immune system and mucus-associated bacteria in health and disease, as well as disease-related peripheral immune signatures indicative of host responses to these organisms. In this brief review, we integrate these novel observations into our overall understanding of host-microbiota mutualism at the colonic mucosal border and speculate on the significance of this emerging knowledge for our understanding of the prevention, development, and progression of chronic intestinal inflammation.